Pengembangan Pemasaran untuk Meningkatkan Kinerja Usaha Rakik Azizah di Kota Padang - Ratni Prima Lita; Agriqisty Agriqisty; Hendra Lukito; Yanti Yanti; Sari Surya; John Edwar; Laela Susdiani; Valeny Suryaningsih; Danny Hidayat (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Universitas Andalas, 2020)
Community Service Activities in Rakik Azizah in Padang City are carried out to identify and solve problems faced by owners in managing and developing Rakik Azizah's. Some of the problems faced by the owner are related to obtaining business licenses, managing business finances, using packaging and marketing. The technique used in carrying out this service activity is through counseling and assistance for the owner of Rakik Azizah. Counseling was carried out during the period the activities were carried out at the Management Department, Universitas Andalas. This extension activity will be followed by demonstration and practice as well as consultation during the period of service to better provide understanding and application of the materials provided in the extension activities that have been carried out. Furthermore, mentoring activities carried out using the vocational method where the community service activity team directly accompanies the operational activities of Rakik Azizah's at the operational location of the business. The activity results are files to administer IPRT, Packaging with attractive labels and increased on line marketing.